(untitled) (Bangladesh Journal of Medical Biochemistry, 2025)
Type 2 diabetes is a common chronic disease resulting from a complex inheritanceenvironment interaction along with other risk factors such as obesity and sedentary lifestyle. Type 2 diabetes and its complications constitute a major worldwide public health problem. The mortality and morbidity increase if there is poor glycemic control. The aim of this study was to compare the BMI and waist circumference in good and poor control type 2 diabetes mellitus. The present study was carried out in departments of Biochemistry, Medicine and Endocrinology of Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh during the period of July 2020 to June 2021. By convenient sampling, a total of 50 subjects aged between 30-59 years were enrolled in this study. Study subjects were divided into two groups. Group A included subjects with good glycemic control (n=25) and Group B included subjects with poor glycemic control (n=25). The mean HbA1c level was significantly higher in poor glycemic control group than good glycemic control group (10.9±5.73% vs 5.98±0.95%). Mean weight, BMI and waist circumference were significantly higher in subjects with poor glycemic control in comparison to subjects with good glycemic control. A strong association was found between obesity indices and diabetes. BMI and WC could be used in clinical practice for suggesting lifestyle modifications. Bangladesh J Med Biochem 2021; 14(2): 43-48